2019
DOI: 10.3390/nu11081885
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Zinc Homeostasis and Interactions: Does Enteric Zinc Excretion Cross-Talk with Intestinal Iron Absorption?

Abstract: Iron and zinc are essential micronutrients required for growth and health. Deficiencies of these nutrients are highly prevalent among populations, but can be alleviated by supplementation and food fortification. Cross-sectional studies in humans showed positive association of serum zinc levels with hemoglobin and markers of iron status. Dietary restriction of zinc or intestinal specific conditional knock out of ZIP4 (SLC39A4), an intestinal zinc transporter, in experimental animals demonstrated iron deficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 88 publications
(133 reference statements)
4
97
0
1
Order By: Relevance
“…65 The balance between intestinal absorption and endogenous loss of Zn through feces is an important pathway for regulating Zn homeostasis. 66 We next demonstrated that a Zn-supplemented diet could significantly protect mice against colitis in two different chemically induced experimental models. In both models, the inhibition of intestinal inflammation (evidenced by fewer clinical signs) was correlated with much lower colonic expression of pro-inflammatory genes and genes involved in oxidative stress.…”
mentioning
confidence: 91%
“…65 The balance between intestinal absorption and endogenous loss of Zn through feces is an important pathway for regulating Zn homeostasis. 66 We next demonstrated that a Zn-supplemented diet could significantly protect mice against colitis in two different chemically induced experimental models. In both models, the inhibition of intestinal inflammation (evidenced by fewer clinical signs) was correlated with much lower colonic expression of pro-inflammatory genes and genes involved in oxidative stress.…”
mentioning
confidence: 91%
“…Both Fe and Ca are physiologically classified as type one nutrients, with inadequacies initially leading to reductions in body stores prior to functional components; while Zn is a type 2 nutrient where declines in plasma levels are observed following observations in clinical symptoms (Kondaiah, Yaduvanshi, Sharp, & Pullakhandam, 2019). This reveals that clinical Zn deficiency can be particularly difficult to detect, due to the absence of an established biomarker (K. Brown et al., 2004).…”
Section: Overview Of Element Bioavailabilitymentioning
confidence: 99%
“…In a similar fashion, enteropancreatic reabsorption (EPR) could not be discarded for weak acids. Although the involvement of this process in drug recirculation has not been reported, pancreatic secretion and reabsorption it has been characterized for ions such as zinc 33 . The pH-driven discrete pancreatic secretion of drugs through acinar cells is highly plausible and its discharge in the duodenum make drug reabsorption a likely scenario.…”
Section: Discussionmentioning
confidence: 99%